The theory of convergent between standard and optimal cost supporting actual cost in an Enterprise: بحث تطبيقي في معمل الألبسة الرجالية في النجف للفترة من 2007-2020 (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to achieve proof of convergence between optimal costs and standard costs in calculating costs for the economic unit, support efforts aimed at adopting optimal costs in cost accounts and accounting thought in general, and achieve benefit from the theory of convergence between optimal costs and standard costs in the field of achieving actual costs in The economic unit in order to reduce and converge, and this came to address the possibility of adopting the concept of optimal costs in the production costs calculations for the purposes of rationalizing administrative decisions, and rationalizing the preparation of financial statements within management accounting.The research concluded that the optimum costs are close in terms of meaning and content with the standard costs, because both were aimed at achieving the optimum utilization of production elements and reaching the zero damage stage and making maximum use of waste or damage at the beginning of the manufacture of atypical products and reducing the actual costs to the lowest level Possible, as well as the research found that the economic unit (the research sample) can benefit from the process of convergence of the concept of standard cost with optimal costs in support of actual costs in practice.